ChemInform Abstract: Design, Synthesis, and in vitro Cancer Cell Growth Inhibition Evaluation and Antimalarial Testing of Trioxanes Installed in Cyclic 2‐Enoate Substructures. Issue 15 (15th April 2014) - Inokuchi, Tsutomu; et al., et al.
Abstract A novel series of trioxanes is synthesized via photooxidation of corresponding 2H‐pyrans and evaluated for their anticancer and antimalarial activities.